Complaints in Menopausal Women and Its Correlation with Lifestyle and Stress - Ni Ketut Alit Armini; Lailatun Ni'mah; Baiq Selly Silviani (Jurnal Ners, 2018)
Introduction: Every woman will have menopausal experiences at the end of a biological process called menstrual cycles. Several complaints can be aggravated by lifestyle and stress. This study was to analyze the relation of lifestyle and stress levels with a menopausal complaint in women.Methods: This study was correlational with a cross-sectional approach. The study involved 101 menopausal women lived in a community selected by proportional random sampling. The independent variables were lifestyle and stress levels in menopausal women. The dependent variable was a menopausal complaint. This study used primary data provided by questionnaires and interviews. The data were analyzed using Spearman’s Rho.Results: There was strong correlation between lifestyle (p=0.000; r=-0.424), stress levels (p=0.000; r=0.535), and complaint in a menopausal woman.Conclusion: A healthy lifestyle, stress-controlled to minimize complaints in menopausal women. Further research is needed on factors that increase stress in postmenopausal women.